2006
DOI: 10.1385/bter:112:3:193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cu and Fe Concentrations on Oxidative Damage in Male Infertility

Abstract: Oxidative stress in the reproductive system is thought to have an effect on the fertilizing ability of sperm. The purpose of this study was to assess the interaction of iron (Fe) and copper (Cu) ions in suspected subfertile and fertile male groups and to find out the relationships of the semen parameters (sperm count, motility, and abnormal morphology), glutathione, malondialdehyde, and reactive oxygen species with these variables. Semen and blood obtained from 60 subfertile men and from 40 fertile volunteers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 31 publications
3
70
3
1
Order By: Relevance
“…For example, consuming 2 servings/wk of fish in lieu of 2 servings/wk of processed red meats was associated with an ;60% higher total normal count (95% CI: 17.9, 117.4). serum leads to decreased sperm motility and morphology (42,43) because of oxidative damage (44). Clearly, this intriguing association deserves further study.…”
Section: Figurementioning
confidence: 99%
“…For example, consuming 2 servings/wk of fish in lieu of 2 servings/wk of processed red meats was associated with an ;60% higher total normal count (95% CI: 17.9, 117.4). serum leads to decreased sperm motility and morphology (42,43) because of oxidative damage (44). Clearly, this intriguing association deserves further study.…”
Section: Figurementioning
confidence: 99%
“…Subanalyses found no differences between fertile and infertile men with respect to age, height, weight, smoking, or alcohol consumption. A study from Turkey collected blood and semen samples from 60 suspected subfertile men attending an infertility clinic and 40 volunteers with normal semen parameters, none of whom had common infertility disorders, drank alcohol, or smoked [Aydemir et al 2006]. Both serum copper (1115 mg/L vs. 941 mg/L) and seminal plasma copper (37 mg/L vs. 34 mg/L) levels were significantly higher in the subfertile group.…”
Section: Essential Metalsmentioning
confidence: 99%
“…Furthermore, Cu can bind directly to free thiols of cysteines (Cys), leading to oxidation and crosslinks between proteins, thus inactivating enzymes or impairing structural proteins (13). Cu induced ROS generation initiate apoptotic/necrotic processes or other pathologies like cancer, neurological diseases, and aging (14). It was found that, multiple sclerosis (MS) subjects had increased levels of Cu in their fluids or brain cells (15).…”
Section: Discussionmentioning
confidence: 99%